Problem:
Given g(x) = 5x + 1, compare and contrast the values of g(-3) and g(-4). Choose the statement that is true concerning the two values.
Solution:
Let g(x) = 5x+ 1, then:
g(-3) = 5(-3) + 1 = -15 + 1= -14
and
g(-4) = 5(-4) +1 = -20+1 = -19
Now, on the real line, the above numbers are represented like this:
Then we can conclude that
![g(-3)=\text{ -14}>-19\text{ = g(-4)}](https://img.qammunity.org/2023/formulas/mathematics/college/gm1zq7fw28tcboddl18jnql6zojblq2tux.png)
That is: the value of g(-3) is larger than the value of g(-4).
Then, we can conclude that the correct answer is : A